Using theory to improve low back pain care in Australian Aboriginal primary care: a mixed method single cohort pilot study. Issue 1 (December 2016) - Lin, Ivan; Coffin, Juli; O'Sullivan, Peter
Abstract Background Low back pain (LBP) care is frequently discordant with research evidence. This pilot study evaluated changes in LBP care following a systematic, theory informed intervention in a rural Australian Aboriginal Health Service. We aimed to improve three aspects of care; reduce inappropriate LBP radiological imaging referrals, increase psychosocial oriented patient assessment and, increase the provision of LBP self-management information to patients. Methods Three interventions to improve care were developed using a four-step systematic implementation approach. A mixed methods pre/post cohort design evaluated changes in the three behaviours using a clinical audit of LBP care in a six month period prior to the intervention and then following implementation. In-depth interviews elicited the perspectives of involved General Practitioners (GPs). Qualitative analysis was guided by the theoretical domains framework. Results The proportion of patients who received guideline inconsistent imaging referrals (GICI) improved from 4.1 GICI per 10 patients to 0.4 (95 % CI for decrease in rate: 1.6 to 5.6) amongst GPs involved in the intervention. Amongst non-participating GPs (locum/part-time GPs who commenced post-interventions) the rate of GICI increased from 1.5 to 4.4 GICI per 10 patients (95 % CI for increase in rate: .5 to 5.3). There was a modest increase in the number of patients who received LBP self-management information from participating GPs and no substantial changes to psychosocial oriented patient assessments by any participants; however GPs qualitatively reported that their behaviours had changed. Knowledge and beliefs about consequences were important behavioural domains related to changes. Environmental and resource factors including protocols for locum staff and clinical tools embedded in patient management software were future strategies identified. Conclusions A systematic intervention model resulted in partial improvements in LBP care. Determinants of practice change amongst GPs were increased knowledge of clinical guidelines, education delivered by someone considered a trusted source of information, and awareness of the negative consequences of inappropriate practices, especially radiological imaging on patient outcomes. Inconsistent and non-evidence based practices amongst locum GPs was an issue that emerged and will be a significant future challenge. The systematic approach utilised is applicable to other services interested in improving LBP care.